Generics, Biosimilars and Follow‐On Non‐Biologic Complex Drugs for Multiple Sclerosis: A Narrative Review of the Regulatory and Clinical Implications for European Neurologists - Berger, Thomas; Zeitlinger, Markus; Popescu, Veronica; Magyari, Melinda; Airas, Laura; Alkhawajah, Mona; Pugliatti, Maura; Zakaria, Magd; Pozzilli, Carlo; Drulovic, Jelena; Van Wijmeersch, Bart; Vermersch, Patrick; et al. (John Wiley & Sons, 2025)
Background
Multiple sclerosis (MS) places substantial socioeconomic burden on patients due to its early onset and progressive nature, but healthcare systems are also impacted by the high costs of disease-modifying treatments (DMTs). The use of generics (for conventional drugs), biosimilars (for biologics) or follow-on versions of non-biologic complex drugs (NBCDs) can help to reduce the cost of MS care and improve patient access. This review describes the European regulatory processes for these DMT ‘copies’ and the available data in people with MS.
Methods
A PubMed literature search was undertaken in March 2024, using the terms ‘biosimilar’, ‘generic’, ‘non-biologic complex drug’, ‘NBCD’ and ‘follow-on’ in association with ‘multiple sclerosis’.
Results
Our literature search identified three clinical studies with generic treatments for MS (two with generic fingolimod and one with generic dimethyl fumarate), 11 studies with biosimilars (eight with biosimilar interferon formulations, one with natalizumab and two with rituximab biosimilars) and six studies with follow-on glatiramer acetate. The data showed that the generics, biosimilars and follow-on NBCDs had similar clinical efficacy and tolerability profiles to the originator drugs, although the quality and quantity of the research varied between DMTs.
Conclusions
In Europe, there are robust regulatory processes for generics, biosimilars and follow-on NBCDs, in order to ensure that these agents can be considered equally effective and safe as the originator DMT. Physicians caring for people with MS should familiarise themselves with the evidence so that they can have informed conversations about the potential use of these agents.